2004
DOI: 10.1159/000075326
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Hearing Impairment on Preverbal Emotional Vocalizations of Infants

Abstract: The aim of the study was to compare the vocalizations of normally hearing and profoundly hearing-impaired infants in the first year of life. After the first recording all hearing-impaired infants were provided with hearing aids. We focused on three issues: (1) Are there different types of preverbal vocalizations in the vocal repertoire of normally hearing and hearing-impaired infants? (2) Do the vocal types emerge at similar age? (3) Does hearing impairment influence the acoustic structure of the preverbal voc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…Elements of this circuitry likely are shared among multiple postinspiratory behaviors, such as swallowing, coughing, and sneezing, that rely on glottis closure (31). In addition, innate vocalizations have been related to nonverbal utterances in humans like laughing, crying, sighing, and moaning, which represent postinspiratory behaviors (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Elements of this circuitry likely are shared among multiple postinspiratory behaviors, such as swallowing, coughing, and sneezing, that rely on glottis closure (31). In addition, innate vocalizations have been related to nonverbal utterances in humans like laughing, crying, sighing, and moaning, which represent postinspiratory behaviors (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on deaf-born human infants have shown that such nonverbal emotional utterances can be produced by infants that had no opportunity to hear and imitate, that is, to learn such utterances. 27 Obviously, nonverbal emotional vocal utterances represent innate vocal patterns, that is, genetically preprogrammed motor patterns. The fact that patients with bilateral lesions in the inferior motor cortex are no more able to speak and sing, but are still able to moan, cry, and laugh, suggests that the motor cortex is indispensable for the production of learned vocal patterns, but is dispensable for the production of innate vocal patterns.…”
Section: U Jü Rgensmentioning
confidence: 99%
“…Unlike the words that make up the segmental aspect of speech, affective vocalizations can be recognized across languages (Laukka et al, 2013), between cultures that have had only minimal historical contact (Sauter et al, 2010)-although with some cultural variation (Scherer and Wallbott, 1994)-and across species (Faragó et al, 2014). Indeed, infants who are hearing-impaired produce affective vocalizations that are acoustically similar to those of normal-hearing infants (Scheiner et al, 2004(Scheiner et al, , 2006. While affective prosody usually unfolds across the course of an utterance, it can also be uttered in the form of short bursts.…”
Section: Introductionmentioning
confidence: 99%